Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
1. 4(x+41)=400
<=>x+41=100
<=>x=59
2.11(x-9)=77
<=>x-9=7
<=>x=16
3.5(x-9)=350
<=>x-9=70
<=>x=79
4.2x-49=3.32
<=>2x=3.32+49
<=>2x=76
<=>x=38
5.200-(2x+6)=43
<=>200-2x-6=64
<=>-2x=64-200+6
<=>-2x=-130
<=>x=65
1) 4(x+41)=400
x+41=400:4
x+41=100
x=100-41
x=59
2) 11(x-9)=77
x-9=77:11
x-9=7
x=7+9
x=16
3) 5(x-9)=350
x-9=350:5
x-9=70
x=70+9
x=79
4) 2x-49=3.3\(^2\)
2x-49=3\(^3\)
2x-49=27
2x=27+49
2x=76
x=76:2
x=38
5, 200-(2x+6)=4\(^3\)
200-(2x+6)=64
2x+6=200-64
2x+6=136
2x=136-6
2x=130
x=130:2
x=65
đúng nha
thanks bn nhìu
a) 150 : [17 - (2x - 3)] = 350
=> 17 - (2x - 3) = \(\frac{150}{350}=\frac{3}{7}\)
=> 2x - 3 = \(17-\frac{3}{7}=\frac{116}{7}\)
=> 2x = \(\frac{116}{7}+3\)
=> 2x = \(\frac{137}{7}\)
=> x = \(\frac{137}{7}:2=\frac{137}{14}\)
b) 4 . [105 - (x - 9)] - 486 = 0
=> 4. [105 - (x - 9)] = 486
=> 105 - (x - 9) = 243/2
=> x - 9 = \(105-\frac{243}{2}=-\frac{33}{2}\)
=> x = \(-\frac{33}{2}+9=-\frac{15}{2}\)
c) 1000 - 2{600 - 4.[198 - 7.(21 - 7)]}.x = 200
=> 1000 - 2{600 - 4.[198 - 7.14]}.x = 200
=> 1000 - 2{600 - 4.[198 - 98].x = 200
=> 1000 - 2{600 - 4.100}.x = 200
=> 1000 - 2{600 -400}.x = 200
=> 1000 - 2.200.x = 200
=> 2.200.x = 800
=> 400.x = 800
=> x = 2
Câu 2 :
a) 350 : [19 - (7x - 3)] = 350
=> 19 - (7x - 3) = 1
=> 7x - 3 = 18
=> 7x = 21
=> x = 3
b) 7.[109 - (x - 9)] - 420 = 0
=> 7.[109 - (x - 9)] = 420
=> 109 - (x - 9) = 60
=> x - 9 = 49
=> x = 49 + 9 = 58
c) 254 - 2{200 - 4.[90 - 7.(19 - 9)]}.x = 54
=> 254 - 2{200 - 4.[90 - 7.10]}.x = 54
=> 254 - 2{200 - 4[90 - 70]} . x= 54
=> 254 - 2{200 - 4.20} . x = 54
=> 254 - 2{200 - 80}.x = 54
=> 254 - 2.120 . x= 54
=> 2.120.x = 200
=> 240.x = 200
=> \(x=\frac{5}{6}\)
a) 71 - (33 + x) = 26
⇔ 71 - 33 - x = 26
⇔ 38 - x = 26
⇔ x = 38 - 26
⇔ x = 12
b) (x + 73) - 26 = 76
⇔ x + 73 - 26 = 76
⇔ x + 47 = 76
⇔ x = 76 - 47
⇔ x = 29
c) 45 - (x + 9) = 6
⇔ 45 - x - 9 = 6
⇔ 36 - x = 6
⇔ x = 36 - 6
⇔ x = 30
d) 89 - (73 - x) = 20
⇔ 89 - 73 + x = 20
⇔ 16 + x = 20
⇔ x = 20 - 16
⇔ x = 4
e) (x + 7) - 25 = 13
⇔ x + 7 - 25 = 13
⇔ x - 18 = 13
⇔ x = 13 + 18
⇔ x = 31
f) 198 - (x + 4) = 120
⇔ 198 - x - 4 = 120
⇔ 194 - x = 120
⇔ x = 194 - 120
⇔ x = 74
g) 140 : (x - 8) = 7
⇔ x - 8 = 140 : 7
⇔ x - 8 = 20
⇔ x = 20 + 8
⇔ x = 28
h) 4(x + 41) = 400
⇔ x + 41 = 400 : 4
⇔ x + 41 = 100
⇔ x = 100 - 41
⇔ x = 59
i) 11(x - 9) = 77
⇔ x - 9 = 77 : 11
⇔ x - 9 = 7
⇔ x = 7 + 9
⇔ x = 16
j) 5(x - 9) = 350
⇔ x - 9 = 350 : 5
⇔ x - 9 = 70
⇔ x = 70 + 9
⇔ x = 79
k) 2x - 49 = 5.32
⇔ 2x - 49 = 45
⇔ 2x = 45 + 49
⇔ 2x = 94
⇔ x = 94 : 2
⇔ x = 47
l) 200 - (2x + 6) = 43
⇔ 200 - 2x - 6 = 64
⇔ 194 - 2x = 64
⇔ 2x = 194 - 64
⇔ 2x = 130
⇔ x = 130 : 2
⇔ x = 65
a) 71 - (33 + x) = 26
⇔ 33+x=71-26
⇔ 33 + x = 45
⇔ x = 45 - 33
⇔ x = 12
Vậy x=12
b) (x + 73) - 26 = 76
⇔ (x + 73) = 76+26
⇔ x + 73 = 102
⇔ x = 102-73
⇔ x = 29
Vậy x=29
c) 45 - (x + 9) = 6
⇔ x + 9 = 45 - 6
⇔ x+9 = 39
⇔ x = 39 - 9
⇔ x = 30
Vậy x=30
\(a)5\left(3-2x\right)+5\left(x-4\right)=6-4x\)
\(\Leftrightarrow5\left(3-2x+x-4\right)=6-4x\)
\(\Leftrightarrow5\left(-x-1\right)=6-4x\)
\(\Leftrightarrow-5x-5=6-4x\)
\(\Leftrightarrow-x=11\Leftrightarrow x=-11\)
Vậy \(x=-11\)
a) (125 -679 + 145 ) - ( 125 - 679 )=125 -679+145-125+679=145
b)(x - 29 ) - ( 17 - 38 ) = -9
<=> x-29 -17+38=-9
<=>x=-1
c)( x + 5 ) + ( x - 9 ) = x + 2
<=>x+5+x-9=x+2
<=>x+x-x=2+9-5
<=>x=6
d) ( 27 - x )+ ( 15 + x ) = x - 24
<=> 27-x+15+x-x=-24
<=> -x=-66
<=>x=66
e) -359 + 181 + ( -123 ) + 350 + ( -172 ) = (181 +350)-(359+172) -123 =531-531-123=-123
f) 13 - 12 + 11 + 10 - 9 + 8 - 7 -6 + 5 - 4 + 3 + 2 -1=( 13 - 12) +11 + (10 - 9)+(8-7)-6+(5-4)+3+(2-1)=1+11+1+1-6+1+3+1=13
a, (125 -679 + 145 ) - ( 125 - 679 )
= 125 - 679 + 145 - 125 + 679
= ( 125 - 125 ) + ( -679 + 679 ) + 145
= 0 + 0 +145
= 145
b, (x - 29 ) - ( 17 - 38 ) = -9
x - 29 - 17 + 38 = -9
x - 29 - 17 = -9 - 38
x - 29 - 17 = -47
x - 29 = -47 + 17
x - 29 = -30
x = -30 + 29
x = -1
Vậy x = -1
c, ( x + 5 ) + ( x - 9 ) = x + 2
x + 5 + x - 9 = x + 2
x - x + 14 = x + 2
14 = x + 2
x = 14 - 2
x = 12
Vậy x = 12
d, ( 27 - x )+ ( 15 + x ) = x - 24
27 - x + 15 + x = x - 24
42 + ( -x + x ) = x - 24
42 = x - 24
x = 24 + 42
x = 66
Vậy x = 66
e, -359 + 181 + ( -123 ) + 350 + ( -172 )
= ( -359 + 350 ) + [ 181 + ( -172 ) ] + ( -123)
= (-9) + 9 + ( -123 )
= 0 + ( -123)
= (-123)
g , 13 - 12 + 11 + 10 - 9 + 8 - 7 -6 + 5 - 4 + 3 + 2 -1
= ( 13 - 12 ) + ( 10 - 9 ) + ( 8 - 7 ) + ( 5 - 4 ) + ( 2 - 1 ) + ( 11 - 6 + 3)
= 1 + 1 + 1 + 1 + 1 + 8
= 1. 5 + 8
= 5 + 8
= 13
1/ 10(X-7)-8(X+5)=6(-5)+24
10x - 70 - 8x - 40 = -30 +24
2x - 110 = -6
2x = 104
x=52
2/ 8(X-|-7|)-6(X-2)=|-8|.6-50
8(x - 7) - 6(x-2) = 8.6 - 50
8x - 56 - 6x +12 =48 -50
2x - 44 = -2
2x = 42
x=21
3/ 2(4X-8)-7(3+X)=|-4|(3-2)
8x-16 - 21 - 7x = 4.1
x-37=4
x=41
4/ 12(X-4)=6(x-2)-16(X+3)=7|-4|
12x - 48 = 6x - 12 - 16x -48 =7.4
12x - 48 = 28
12x=76
x=19/3
5/ 4(X-5)-7(5-X)+10(5-X)=-3
4x - 20 -35 +7x + 50 -10x = -3
x - 5 = -3
x = -2
Chúc bạn học tốt!
47. (23 + 50)- 23. ( 47+50 )
= 47. 23+ 47. 50- 23. 47 - 23. 50
=47. 50 - 23. 50
= 50 .( 47 -23)
=50. 24 = 1200
Bạn ơi k có quy luật